Experimental damage detection in smart structures using lamb waves approach - Franco, Vitor Ramos [UNESP]; Bueno, Douglas Domingues [UNESP]; Marqui, Clayton Rodrigo [UNESP]; Lopes, Vicente [UNESP] (My University, 2008)
This paper presents an experimental technique for structural health monitoring (SHM) based on Lamb waves approach in an aluminum plate using piezoelectric material as actuators and sensors. Lamb waves are a form of elastic perturbation that remains guided between two parallel free surfaces, such as the upper and lower surfaces of a plate, beam or shell. Lamb waves are formed when the actuator excites the surface of the structure with a pulse after receiving a signal. Two PZTs were placed in the plate surface and one of them was used to send a predefined wave through the structure. Thus, the other PZT (adjacent) becomes sensor and measurer of the reply signals receiving the pulses. Using this methodology, this paper presents one case of damage detection considering the aluminum plate in the free-free-freefree boundary condition. The damage was simulated by adding additional mass on the plate. It is proposed two damage detection indexes obtained from experimental involving the Fast Fourier Transform (FFT) and the power spectral density (PSD) computed using the output signal. The results show the viability of the presented methodology to damage detection in smart structures.
Keywords: Frequency domain; Lamb waves; Smart structures; Structural healthy monitoring